The "Cyprus Problem" and the President and Parliament in the "Turkish Republic of Northern Cyprus" - Jonathan Warner (Czasopismo Prawno-Historyczne)
Any account of the history of Cyprus, and the so-called Cyprus Problem involves contested narratives, and so is likely to be long in order to reflect fully the nuances of the different stories produced by the two communities, Greek and Turkish. At base, the recent history of Cyprus demonstrates that building a multi-ethnic state is never easy, especially when there is no strong national identity, and instead the various groups owe allegiance elsewhere.